Detection of 2019 novel coronavirus in semen and testicular biopsy specimen of COVID-19 patients - Ci Song; Yan Wang; Weiqin Li; Bicheng Hu; Guohua Chen; Ping Xia; Wei Wang; Chaojun Li; Zhibin Hu; Xiaoyu Yang; Bing Yao; Yun Liu (2020)
Abstract Background As of March 11, 2020, the COVID-19 outbreak was declared as a pandemic. Expending our understanding of the transmission routes of the viral infection is crucial in controlling the outbreak. It is unclear whether the 2019 novel coronavirus (2019-nCoV) can directly infect the testes or male genital tract and be sexually transmitted from males. Methods From January 31 to March 14, 2020, 12 patients in recovery and one patient died of COVID-19 were included in this descriptive study. The clinical characteristics, laboratory findings, chest CT scans and outcome data were recorded. To examine whether there is sexual transmission from male, we employed realtime polymerase chain reaction testing (RT-PCR) to detect 2019-nCov in semen or testicular biopsy specimen. Findings The age range of the 12 patients in recovery was 22-38 years. None of the patients developed severe COVID-19 pneumonia. As of March 14, 2020, ten patients discharged from the hospital while the rest 2 had developed into recovery stage. All of the 12 patients in recovery tested negative for 2019-nCoV RNA in semen samples. Another patient aged 67 died in March 10, 2020, whose tissue sample via testicular biopsy was also tested negative for viral RNA. Conclusion No positive RT-PCR result was found in the semen or testicular biopsy specimen. The results from this study show no evidence of sexual transmission of 2019-nCov from males.